Stabilization studies of EAF slag for its use as materials in construction - Yang, Qixing; Haase, Björn; Engström, Fredrik; Björkman, Bo (Luleå tekniska universitet, Mineralteknik och metallurgi, 2012)
At Halmstadsverken, the steel plant of Höganäs AB in Sweden, steel grades with low carbon contents were produced using an Electric Arc Furnaces (EAF). Very often, the tapped EAF slag disintegrated during cooling. Slag fines from the disintegration are difficult to handle and to use as materials for construction purposes. MiMeR, Minerals and Metals Recycling Research Centre at Luleå University of Technology (LTU), has, in a close cooperation with Höganäs AB, performed test work to treat the EAF slag. The study has been performed within the research program “Towards a Closed Steel Ecocycle”, carried out by Jernkontoret, with financial support from the Foundation for Environment Strategic Research in Sweden. Some of the projects in the program are aimed at enhancing utilizations of steelmaking slags as building materials. In the first study stage, the EAF slag samples, mixed together with stabilizers, were melted at 1610ºC and then cooled in a crucible system. The liquid EAF slag was also cooled rapidly by air using a laboratory granulation system. In the second study stage, by referring to the early results, two test campaigns were carried out at Halmstadsverken to stabilize EAF slag using a stabilizing additive, high in P2O5. The slag after the stabilization was cooled in air and by water, providing slag samples of large quantities for later long-term aging and stability tests. Test operations were performed without disturbing the normal EAF steel production. In this paper, some of the details of test operations are described and results obtained from the two study stages are presented and discussed. Godkänd; 2012; 20130110 (yang)